(untitled) (Hematology Meeting Reports, 2009)
Bortezomib, the first of its class of new agents called proteasome inhibitors, was approved by the FDA initially as third line therapy in multiple myeloma (MM) in May 2003 and added early 2005 as second line option in this disease. In parallel activity of bortezomib has been shown in a variety of lymphomas especially in mantle cell and follicular lymphoma subtypes. Though inhibitors of the proteasome can be considered as targeted agents (i.e. affecting a discrete enzymatic subunit in the UPP pathway), the antitumor effect of proteasome inhibitors results from the disruption of multiple pathways in cancer cells (cell cycle, cell survival, growth and differentiation) as well as on microenvironment (adhesion molecules and angiogenesis).